PERANAN PENDIDIKAN FORMAL DALAM PROSES PEMBUDAYAAN - Juanda (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2010)
This article deals the role of formal education in the process of enculturation, including six aspects: education and encul-turation, educational policy in Indonesia, educational aspects as cultural phenomena, the functions of culture in education, the role of formal education in the process of enculturation, and the process of enculturation through formal education. The policy of equal right for education is designed to give equal opportunity to all people to get education without discrimination to any ethnic group. Education is an endeavour of developing the community culture to be a modern society, developed and harmonious based on the shared cultural values. Enculturation process is an attempt to guide someone’s attitude and behaviour based on science and skill.